Do not forsake the assembly: The importance of Christian community - Dibley, Peter (Review and expositor, 2018)
The Church in America (Orthodox, Catholic, and Protestant) is facing a critical challenge in the twenty-first century. That challenge is that more and more people are leaving Church. Research has found that of the 73% of Americans who call themselves Christian only 31% go to church at least once a month. Those who are leaving the Church fall into three groups: "those who love Jesus, but not the Church," "Church refugees," and "dones." Each of these groups shares a few common bonds. They are discouraged and fed up with being hurt by other Christians and being stifled by Church bureaucracy. Most of all they are discouraged by what they feel to be a lack of community in the Church. Thus, they are finding community in other places outside the Church. The Bible has a lot to say about the importance of Christian community, and specifically the community of the Church. This article explores passages in both the First and Second Testaments that strongly encourage community and set forth the benefits of community, especially within the Church. The article also presents an example within a local church about the care, love, and support a family experienced during a time of crisis from the church. In addition, the article also emphasizes how important it is to give witness to how the Church rallies to form community. The family shared their story and their expression of gratitude to the church. This article tells their story to inspire and offer hope to those who have gone through tragedy and have given up on the Church.